RAPID SEA-LEVEL RISE IN THE NORTH ATLANTIC OCEAN SINCE THE FIRST HALF OF THE NINETEENTH CENTURY - Gehrels W.R.; Marshall W.A.; Gehrels M.J.; Larsen G.; Eiríksson J.; Kirby J.R.; Heinemeier J.; Shimmield T. (My University, 2006)
A high-resolution late-Holocene sea-level record is produced from salt-marsh deposits at Vioarhólmi in Snæfellsnes, western Iceland. The stratigraphy of Vioarhólmi saltmarsh is documented using detailed descriptions of ten exposed sections and numerous hand-drilled cores. Fossil foraminifera are used as proxy sea-level indicators in an exposed section of salt-marsh peat. The agglutinated foraminifera Jadammina macrescens and Paratrochammina (Lepidoparatrochammina) haynesi are most useful as sea-level indicators because of their narrow vertical extent on the marsh surface and their good preservation in the peaty marsh deposits. We collected compaction-free sea-level index points from salt-marsh peat directly overlying the bedrock surface to establish the pre-industrial millennial-scale trend of sea-level rise and evaluate effects of autocompaction on the stratigraphy. The chronology of the sea-level reconstruction is based on tephra stratigraphy, AMS 14C, 137Cs, Pb and palaeomagnetic analyses. The main tephra layer visible in the stratigraphy of Vioarhólmi salt marsh is the Landnám (settlement) layer, previously dated to AD 875±6. A sea-transported pumice layer was correlated to the 'Mediaeval Layer' of AD 1226/27. Our reconstruction indicates that relative sea level along the coast of western Iceland has risen by about 1.3 m since c. AD 100. The detrended sea-level record shows a slow rise between AD 100 and 500, followed by a slow downward trend reaching a lowstand in the first half of the nineteenth century. This falling trend is consistent with a steric change estimated from reconstructions of sea-surface and sea-bottom temperatures from shelf sediments off Northern Iceland. The sea-level record shows a marked recent rise of about 0.4 m that commenced AD 1820±20 as dated by palaeomagnetism and Pb produced by European coal burning. This rapid sea-level rise is interpreted to be related to global temperature rise. The rise has continued up to the present day and has also been measured, since 1957, by the Reykjavik tide gauge. © 2006 SAGE Publications.
Keywords: DATING; HOLSMEER PROJECT; ICELAND; LATE HOLOCENE; SALTMARSH; SEA-LEVEL CHANGE; TEPHRA; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен